2016
DOI: 10.1016/j.physd.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between consensus and coherence in a model of interacting opinions

Abstract: The formation of agents' opinions in a social system is the result of an intricate equilibrium among several driving forces. On the one hand, the social pressure exerted by peers favours the emergence of local consensus. On the other hand, the concurrent participation of agents to discussions on different topics induces each agent to develop a coherent set of opinions across all the topics in which he is active. Moreover, the prevasive action of external stimuli, such as mass media, pulls the entire population… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
1
16
0
1
Order By: Relevance
“…F. Battiston et al have also studied the heterogeneity effect depending upon the voter model [62]. They have found that the relative weight assigned to social pressure, internal coherence and external mean-field force has a great impact on the occurrence of phase transitions between a disordered system and an ordered system, which is similar to the role of the heterogeneous influence of peer pressure in our model.…”
Section: Discussionsupporting
confidence: 72%
“…F. Battiston et al have also studied the heterogeneity effect depending upon the voter model [62]. They have found that the relative weight assigned to social pressure, internal coherence and external mean-field force has a great impact on the occurrence of phase transitions between a disordered system and an ordered system, which is similar to the role of the heterogeneous influence of peer pressure in our model.…”
Section: Discussionsupporting
confidence: 72%
“…where i x is the coherence of the strategies of player i. across the M different layers. A similar definition of coherence for the particular case M = 2 has been reported in [78]. In addition to the two main order parameters c and ξ, when M = 2, we will also use the quantities c c…”
Section: Public Goods Game In the Multiplexmentioning
confidence: 98%
“…The first papers on the subject have focused on the characterization of the structure of multiplex networks [16][17][18][19][20][21][22][23][24][25][26][27][28], and on modeling the basic mechanisms of their growth [29][30][31][32][33]. In parallel to this, some effort has been also devoted on investigating various kinds of dynamical processes on multiplex topologies, including diffusion [34][35][36][37][38], epidemic spreading [39][40][41][42][43][44], cooperation [45][46][47][48], opinion formation [49][50][51][52], and percolation [46,[53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%